Changing Political and Societal Discourse in the Context of NATO Accession: A Focus on Finland - Lyytikäinen, Minna; Ketola, Johanna; Vastapuu, Leena (Bristol University Press, 2026)
This chapter examines Finland’s decision to apply for NATO membership following Russia’s full-scale invasion of Ukraine in February 2022, revealing key paradoxes in Finnish foreign and security policy and its gender equality regime. Building on feminist International Relations scholarship, we identify two forms of gendered silencing in the political decision-making process: the exclusion of women and their agency in policy making, and the absence of gender equality concerns in foreign and security policy, reflected in the marginalization of the Women, Peace and Security (WPS) agenda. Drawing on government reports, parliamentary debates and data on gender balance in decision-making, the chapter analyses the period between 24 February and 18 May 2022, arguing that the crisis exposed deeper silences and structural inequalities embedded within Finland’s foreign and security policy making.
Critical Perspectives on NATO: Feminist insights